2010
DOI: 10.1161/circresaha.109.212753
|View full text |Cite
|
Sign up to set email alerts
|

Defective DNA Replication Impairs Mitochondrial Biogenesis In Human Failing Hearts

Abstract: Rationale: Mitochondrial dysfunction plays a pivotal role in the development of heart failure. Animal studies suggest that impaired mitochondrial biogenesis attributable to downregulation of the peroxisome proliferator-activated receptor ␥ coactivator (PGC)-1 transcriptional pathway is integral of mitochondrial dysfunction in heart failure. Objective: The study sought to define mechanisms underlying the impaired mitochondrial biogenesis and function in human heart failure. Methods and Results: We collected lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
166
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(184 citation statements)
references
References 38 publications
15
166
2
1
Order By: Relevance
“…An additional known target of AMPK, estrogen-related receptor α (ERRα) expression (26), was also decreased in banded Chip -/-hearts (Supplemental Figure 3C). ERRα regulates mitochondrial biogenesis independently of PGC1-α (26,27), and our observation of decreased ERRα and PGC1-α expression is consistent with reduced AMPK function and decreased mitochondrial biogenesis in banded Chip -/-hearts. These results indicate that, despite allosteric cues (increased ADP/ ATP ratio) and increased expression of LKB1, AMPK activation and activity are significantly diminished in banded Chip -/-hearts, suggesting that either proteins regulated by CHIP or CHIP itself plays a key role in AMPKα activation and activity toward downstream targets during cardiac pressure overload.…”
Section: Figuresupporting
confidence: 86%
“…An additional known target of AMPK, estrogen-related receptor α (ERRα) expression (26), was also decreased in banded Chip -/-hearts (Supplemental Figure 3C). ERRα regulates mitochondrial biogenesis independently of PGC1-α (26,27), and our observation of decreased ERRα and PGC1-α expression is consistent with reduced AMPK function and decreased mitochondrial biogenesis in banded Chip -/-hearts. These results indicate that, despite allosteric cues (increased ADP/ ATP ratio) and increased expression of LKB1, AMPK activation and activity are significantly diminished in banded Chip -/-hearts, suggesting that either proteins regulated by CHIP or CHIP itself plays a key role in AMPKα activation and activity toward downstream targets during cardiac pressure overload.…”
Section: Figuresupporting
confidence: 86%
“…Indeed, Ppargc1a/b-knockout mice have reduced cardiolipin and impaired mitochondrial respiration. Third, a number of studies in animal models and in humans have shown reduced levels of PGC-1α and ERR transcripts and protein levels in heart failure (117)(118)(119)(120)(121). Collectively, these data clearly connect diminished mitochondrial respiration capacity with reduced ERR/PGC-1 signaling and suggest that this may be a final common pathway in heart failure ( Figure 3).…”
Section: Energy Metabolic Derangements In the Failing Heartmentioning
confidence: 85%
“…In the failing ventricular myocard from patients with end-stage heart failure a marked decline in mitochondrial Mn-SOD protein and activity is detected [138]. Mitochondrial biogenesis is also severely impaired as evidenced by reduced mtDNA replication and depletion of mtDNA in the human failing heart [139].…”
Section: Mitochondrial Ros Production and Angiotensin II In Cardiac Fmentioning
confidence: 99%